Developing an Inclusive Conceptual Model for Preventing Violence in the Home in Humanitarian Settings: Qualitative Findings From Myanmar and the Democratic Republic of Congo. Issue 3 (February 2022) - Falb, Kathryn; Asghar, Khudejha; Pardo, Natalia Maria; Hategekimana, Jean De Dieu; Kakay, Haja; Roth, Danielle; O'Connor, Meghan
This qualitative study sought to explore the shared risk factors and social norms that may underpin the co-occurrence of intimate partner violence, child maltreatment, and violence against other marginalized household members in the home. Data are drawn from participants who completed either in-depth interviews ( N = 51 men, N = 52 women participants) or focus groups ( N = 22 men, N = 23 women participants) and were living in two distinct humanitarian settings: North Kivu, Democratic Republic of the Congo, and Northern Shan State and Southern Kachin State, Myanmar. Within this overarching objective, attention to these shared drivers for violence in the home, which may arise from people having multiple and interacting social identities, such as disability status, gender, and age, was explored through an inclusion lens and inductive coding approaches. Findings point to risk factors of violence in the home at all levels of the ecological model, which are underpinned at the macro level by gender inequality, armed conflict, and political instability, among other factors. With the community and family levels, gender inequality manifested in norms related to the acceptability of violence, family reputation, and aged and gendered power hierarchies within the home. Shared risk factors of violence at these levels also included displacement/migration-related stressors, inconsistent income, and lack of community resources to support families, especially for those with disabilities. At the most time-proximal level, interactions between role (non)fulfillment, inability of families to meet their basic needs, alcohol and substance abuse, and abusive expressions of anger were found to catalyze instances of violence in the home. The conceptual model also illuminates potential levers and inclusive entry points that prevent violence in the home for diverse women, children, persons with disabilities, and older persons. Key attention to addressing gender inequality and acceptance of violence must be a cornerstone of sustainable programming, alongside complementary approaches that address other shared risk factors.